A20 protects neuronal apoptosis stimulated by lipopolysaccharide-induced microglial exosomes. (1st November 2019) - Chen, Xiaoqing; Qian, Boyu; Kong, Xiaoli; Hao, Jie; Ye, Yong; Yang, Kai; Xu, Tianli; Zhang, Feng
Highlights: First, we report for the first time that provide the experimental evidence to understand the mechanism by which microglial exosomes regulate neuronal inflammation after traumatic brain injury, this study primarily analyzed the effect of microglial exosomes on neuronal apoptosis. Second, the exosomes derived from lipopolysaccharide (LPS)-activated microglial cultures were identified and purified. Neurons treated with these exosomes underwent apoptosis. Also, our results confirmed directly that A20 knockdown increased the exosome-induced neuronal death. Thus, these data highlighted that exosomes may be critical for communication between microglia and neurons. Abstract: LPS-induced microglial activation has a major influence on neuronal damage in the inflammatory process. Integral to this is the cellular and molecular interaction between microglia and neurons. Exosomes, a mediator of communication between cells, can transfer lipids, proteins and nucleic acids, affecting many donor and recipient cells. To investigate the mechanism by which microglial exosomes regulate neuronal inflammation after traumatic brain injury, this study primarily analyzed the effect of microglial exosomes on neuronal apoptosis. Exosomes derived from lipopolysaccharide (LPS)-activated microglial cultures were identified and purified. Neurons treated with these exosomes underwent apoptosis. A20 (also known as TNF-inducible protein 3, TNFAIP3) is a deubiquitinating enzyme with key anti-inflammatory functions. A20 is of huge significance to the degeneration and development of neuron. Importantly, A20 protects the exosomes-induced neuronal death, while A20 knockdown increases neuronal death. This study shows that exosomes may be critical for communication between microglia and neurons.